Are tall people less risk averse than others? - Olaf Hübler (Institute for the Study of Labor (IZA), 2012)
This paper examines the question of whether risk aversion of prime-age workers is negatively correlated with human height to a statistically significant degree. A variety of estimation methods, tests and specifications yield robust results that permit one to answer this question in the affirmative. Hausman-Taylor panel estimates, however, reveal that height effects disappear if personality traits and skills, parents' behaviour, and interactions between environment and individual abilities appear simultaneously. Height is a good proxy for these influences if they are not observable. Not only one factor but a combination of several traits and interaction effects can describe the time-invariant individual effect in a panel model of risk attitude.
urn:nbn:de:101:1-201207126924
Keywords: D90; J13; J24; 330; height; risk preference; Risikoprämie; Biologische Daten; Schätzung; Deutschland